Corrosion-resistant duplex stainless steel pipe for ocean engineering and preparation method of corrosion-resistant duplex stainless steel pipe

By applying modified coatings on the surface of duplex stainless steel pipes and using materials such as zinc oxide and epoxy resin to form covalent bonds, the problem of insufficient corrosion resistance in marine engineering is solved, and higher corrosion resistance and service life are achieved.

CN119592186AInactive Publication Date: 2025-03-11JIANGYIN SOUTH STAINLESS STEEL PIPES CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411757649.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The corrosion resistance of duplex stainless steel in marine engineering applications needs to be further improved, especially in harsh service environments, the existing technology is difficult to effectively prevent rapid damage caused by local corrosion.

Method used

By applying a modified coating on the surface of duplex stainless steel pipes, the coating consists of zinc oxide, epoxy resin, isocyanate-based end-ended polyurethane, etc., it forms covalent bonds and modified structures through chemical reactions and physical mixing, thereby improving adhesion and corrosion resistance.

Benefits of technology

It significantly improves the corrosion resistance of duplex stainless steel pipes, extends service life, reduces the risk of local corrosion, and improves the adhesion and stability of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592186A_ABST
    Figure CN119592186A_ABST
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant duplex stainless steel pipe for ocean engineering and a preparation method of the corrosion-resistant duplex stainless steel pipe, belongs to the technical field of duplex stainless steel, and aims to solve the problem that the corrosion resistance of duplex stainless steel in ocean engineering application needs to be further improved in the prior art. The preparation method of the corrosion-resistant duplex stainless steel pipe for ocean engineering comprises the following steps: reacting zinc oxide with 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine, so as to obtain zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine; zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine and the epoxy modified carbon fiber are subjected to a reaction, and modified zinc oxide is obtained; and uniformly coating the treated duplex stainless steel surface with a coating obtained by uniformly mixing modified polyurethane, a defoaming agent, deionized water, a film-forming agent, a curing agent and an adhesion promoter, and heating and curing to obtain the corrosion-resistant duplex stainless steel pipe for ocean engineering. The corrosion-resistant duplex stainless steel pipe for ocean engineering has excellent corrosion resistance, chemical resistance and durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of duplex stainless steel, and in particular to a corrosion-resistant duplex stainless steel pipe for marine engineering and a preparation method thereof. Background Art

[0002] Duplex stainless steel is an important type of stainless steel. It is composed of ferrite and austenite. It combines the advantages of ferrite and austenite steels, and has good mechanical properties and corrosion resistance. It is widely used in the fields of marine oil and gas transportation and coal chemical industry. It is more widely used in marine engineering, oil and gas transportation, chemical ship manufacturing, nuclear power and other fields. With the further expansion of people's demand for expanding marine space and energy mining, the environment for the application of duplex stainless steel is becoming more and more harsh; especially in the harsh service environment, it maintains good corrosion resistance. Stainless steel pipes are placed in the sea for a long time. The outer wall of the steel pipe is in contact with seawater for a long time, and the corrosiveness of seawater is strong, so the outer wall of the steel pipe is easily corroded, and the working time is limited. Among them, the corrosion of steel pipes mainly includes pitting corrosion, crevice corrosion, intergranular corrosion and stress corrosion. The corrosion types of duplex stainless steel can be simply divided into uniform corrosion and local corrosion; local corrosion is concentrated in individual locations for rapid corrosion damage, which is highly concealed and difficult to detect, and is more harmful than uniform corrosion. At present, the investigation results of various corrosion failure accidents show that uniform corrosion accounts for only about 20%, and local corrosion accounts for as much as 80%. For the corrosion protection of stainless steel, people often use surface coating to reduce the damage of stainless steel pipes; for duplex stainless steel pipes commonly used in marine engineering, people will pay more attention to optimizing the composition of the stainless steel material itself. However, this method has the problem of high investment cost and long research time.

[0003] Chinese patent CN111718642B discloses a high adhesion powder coating for stainless steel and a preparation method thereof, wherein the high adhesion powder coating for stainless steel is prepared by mixing carboxyl polyester resin, hydroxyl polyester resin, epoxy resin modified by silicone coupling agent, polyhydroxy compound modified by silicone coupling agent, curing agent and auxiliary agent in a mass ratio of (40-70):(2-12):(2-15):(1.5-10):(2-5):(20-40) by mass percentage. The corrosion resistance of the powder coating prepared in this way for stainless steel needs to be improved. Chinese patent CN108178984B discloses a high temperature resistant heavy anti-corrosion coating for stainless steel, wherein a modified epoxy silicone resin, an additive I and an inorganic pigment filler are mixed in a mass ratio of (25-40):2:(58-73) to obtain component A; a modified alicyclic amine and an additive II are mixed in a mass ratio of (99-99.5):(0.5-1) to obtain component B; component A and component B are mixed in a mass ratio of 100:(2.2-3.52) to obtain a high temperature resistant heavy anti-corrosion coating for stainless steel, but there is a problem that the compatibility between the coating components needs to be further improved. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a corrosion-resistant duplex stainless steel pipe for marine engineering and a preparation method thereof, which solves the problem in the prior art that the corrosion resistance of duplex stainless steel in marine engineering applications needs to be further improved.

[0005] In order to achieve the above object, the present invention provides a method for preparing a corrosion-resistant duplex stainless steel pipe for marine engineering, comprising the following steps:

[0006] Step (1) in an inert gas, zinc oxide and 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine are added to N,N-dimethylformamide, potassium carbonate is added, heating is performed, reacting is performed, the reaction is completed, filtering is performed, washing is performed, and drying is performed to obtain zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine;

[0007] Step (2) adding epoxy-modified carbon fiber and zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine to a hydrochloric acid aqueous solution, heating, reacting, filtering, washing, and drying after the reaction is completed to obtain modified zinc oxide;

[0008] Step (3) adding epoxy resin and modified zinc oxide into toluene, heating, reacting, filtering, washing and drying after the reaction is completed to obtain modified zinc oxide grafted epoxy resin;

[0009] Step (4) adding the isocyanate-terminated polyurethane and the modified zinc oxide-grafted epoxy resin into acetone, adding a catalyst, reacting, filtering after the reaction is completed, washing, and drying to obtain a modified polyurethane;

[0010] The modified polyurethane, defoamer, deionized water, film former, curing agent and adhesion promoter are uniformly mixed to obtain a coating;

[0011] Step (5) polishes, rinses and blows the surface of the duplex stainless steel, uniformly applies the coating on the treated surface of the duplex stainless steel, heats and solidifies it, and obtains a corrosion-resistant duplex stainless steel pipe for marine engineering.

[0012] Preferably, the mass ratio of zinc oxide, 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine, N,N-dimethylformamide and potassium carbonate is (60-80):(250-370):(2000-4000):(60-80); the reaction temperature is 45-65°C, and the reaction time is 34-46h.

[0013] Preferably, the mass ratio of epoxy modified carbon fiber, zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine and hydrochloric acid aqueous solution is (20-40):(500-800):(6000-10000); the reaction temperature is 65-85°C, the reaction time is 2-4h; and the concentration of hydrochloric acid aqueous solution is 0.01mol / L.

[0014] Preferably, the mass ratio of epoxy resin, modified zinc oxide and toluene is (200-400):(80-100):(2000-4000); the reaction temperature is 60-80° C., and the reaction time is 3-5 h.

[0015] Preferably, the mass ratio of isocyanate-terminated polyurethane, modified zinc oxide grafted epoxy resin, acetone and catalyst is (100-180):(400-600):(2500-4500):(1.5-2.7); the reaction temperature is 80-100° C., and the reaction time is 26-38 h.

[0016] Preferably, the catalyst is dibutyltin dilaurate.

[0017] Preferably, the method for preparing the isocyanate-terminated polyurethane comprises the following steps:

[0018] Add dimethylbiphenyl diisocyanate and 1,4-butanediol to a solvent, stir evenly, heat, react, add a protective agent, react, and after the reaction is completed, perform reduced pressure distillation to obtain an intermediate I;

[0019] The intermediate I is added to tetrahydrofuran, methanol is added, filtered, washed, and dried to obtain an isocyanate-terminated polyurethane;

[0020] Wherein, the solvent is any one of dimethyl sulfoxide, toluene and tetrahydrofuran;

[0021] Wherein, the molar ratio of dimethylbiphenyl diisocyanate, 1,4-butanediol and solvent is (2-3):(0.8-1):(30-40);

[0022] The temperature of the first reaction is 75-85°C and the reaction time is 11-13h; the temperature of the second reaction is 95-115°C and the reaction time is 9-11h;

[0023] Wherein, the mass ratio of intermediate I, tetrahydrofuran, methanol and deionized water is (2-4):(10-18):(3-5):(8-10); the drying temperature is 95-115°C, and the drying time is 14-16h;

[0024] The reduced pressure distillation conditions are: distillation at 0.08 MPa and 80-95°C for 10-14 hours.

[0025] Wherein, the protective agent is caprolactam.

[0026] Preferably, the method for preparing epoxy-modified carbon fiber comprises the following steps:

[0027] The carbon fiber, anhydrous ethanol and γ-(2,3-epoxypropoxy)propyltrimethoxysilane are uniformly mixed, heated, reacted, centrifuged, washed and dried to obtain epoxy-modified carbon fiber;

[0028] Among them, the mass ratio of carbon fiber, anhydrous ethanol and γ-(2,3-epoxypropoxy)propyltrimethoxysilane is (20-30):(1500-3500):(6-10); the reaction temperature is: 60-80°C, and the reaction time is 3-5h.

[0029] Preferably, the mass ratio of modified polyurethane, defoamer, deionized water, film former, curing agent and adhesion promoter is (50-60):(0.2-0.6):(12-20):(3-5):(10-20):(1-2).

[0030] Preferably, the defoamer is BYK-024.

[0031] Preferably, the adhesion promoter is a silane-based adhesion promoter.

[0032] Preferably, the film-forming agent is one or a combination of two or more of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate and 1-phenoxy-2-propanol.

[0033] Preferably, the curing agent is ethylenediamine.

[0034] Preferably, the corrosion-resistant duplex stainless steel pipe for marine engineering is prepared by the method for preparing the corrosion-resistant duplex stainless steel pipe for marine engineering.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] 1. The epoxy resin used in the present invention has certain wear resistance, good thermal stability and chemical resistance. The epoxy group contained in the epoxy resin can react chemically with the hydroxyl group on the metal surface to form a covalent bond and has good adhesion. The zinc oxide in the present invention is a nanostructure and can be used as a filler to fill the gaps in the epoxy resin, prolong the path for water or corrosive ions to enter the coating, and prolong the time for contact with the metal surface to cause metal damage. Due to the nano-size effect, nano zinc oxide has the ability to scatter ultraviolet rays and can play an anti-ultraviolet role. The introduced 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine can convert the energy of ultraviolet rays into harmless low-radiation heat energy and release it, which has certain anti-ultraviolet performance. Adding both at the same time can enhance the anti-ultraviolet performance of the epoxy resin. The hydroxyl group on the surface of zinc oxide reacts with the chlorine group in 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine to generate a more chemically resistant ether group, which increases the compatibility of zinc oxide. Adding it to the epoxy resin further increases the chemical resistance, heat resistance and stability. Zinc oxide is evenly dispersed in the epoxy resin matrix, which greatly improves the wear resistance of the matrix, effectively avoids the phenomenon of fine cracks in the epoxy resin matrix after long-term use in harsh environments, and further improves the service life of the coating.

[0037] 2. The epoxy group in the epoxy-modified carbon fiber of the present invention reacts with the amino group in the zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine to obtain a modified zinc oxide containing amino groups and hydroxyl groups; the epoxy group in the epoxy resin reacts with the amino group in the modified zinc oxide to obtain a modified zinc oxide grafted epoxy resin; the hydroxyl group in the modified zinc oxide grafted epoxy resin reacts with the isocyanate group in the isocyanate-terminated polyurethane under the action of a catalyst to obtain a modified polyurethane, which greatly increases the compatibility of the epoxy resin with the polyurethane with good flexibility and strong impact resistance, and is evenly dispersed to avoid uneven corrosion protection, and reduce the probability of pitting of steel pipes in marine engineering. Carbon fiber has high thermal stability and is not easy to deform or degrade. The low thermal expansion characteristics of carbon fiber can help the coating remain stable in an environment with extreme temperature differences and reduce cracking or peeling of the coating caused by temperature changes. The modified polyurethane has good fluidity and can effectively diffuse and cover the surface of the substrate, filling tiny cracks and pores, thereby increasing the contact area, further enhancing adhesion and extending the service life of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a process flow chart of the preparation of corrosion-resistant duplex stainless steel pipe for marine engineering in the present invention;

[0039] Figure 2 This is a schematic diagram of the reaction for preparing zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine in the present invention;

[0040] Figure 3 Schematic diagram of the reaction for preparing modified zinc oxide in the present invention. DETAILED DESCRIPTION

[0041] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Example 1

[0043] This embodiment provides a method for preparing epoxy-modified carbon fiber, comprising the following steps:

[0044] Carbon fiber, anhydrous ethanol and γ-(2,3-epoxypropoxy)propyltrimethoxysilane were mixed in a mass ratio of 20:1500:6, reacted at 60°C for 5 hours, and after the reaction was completed, centrifuged, washed with deionized water, and dried at 90°C for 5 hours to obtain epoxy-modified carbon fiber.

[0045] Example 2

[0046] This embodiment provides a method for preparing an isocyanate-terminated polyurethane, comprising the following steps:

[0047] Under a nitrogen atmosphere, dimethylbiphenyl diisocyanate, 1,4-butanediol and dimethyl sulfoxide were mixed in a molar ratio of 2:0.8:30, stirred, reacted at 75°C for 13 hours, caprolactam was added, reacted at 95°C for 11 hours, and after the reaction was completed, distilled at 0.08 MPa and 95°C for 10 hours to obtain intermediate I;

[0048] The intermediate I is added to tetrahydrofuran, methanol is added, filtered, washed with deionized water, and dried at 100° C. for 15 h to obtain an isocyanate-terminated polyurethane;

[0049] Wherein, the mass ratio of intermediate I, tetrahydrofuran, methanol and deionized water is 2:10:3:8.

[0050] Example 3

[0051] This embodiment provides a method for preparing a corrosion-resistant duplex stainless steel pipe for marine engineering, comprising the following steps:

[0052] Step (1) under an argon atmosphere, zinc oxide, 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine, N,N-dimethylformamide and potassium carbonate are mixed in a mass ratio of 60:250:2000:60, reacted at 45°C for 46 hours, filtered, washed with anhydrous ethanol, and dried at 80°C for 6 hours to obtain zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine;

[0053] Step (2) epoxy modified carbon fiber, zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine and 0.01 mol / L hydrochloric acid aqueous solution are mixed in a mass ratio of 20:500:6000, reacted at 65°C for 4h, filtered, washed with deionized water, and dried at 70°C for 8h to obtain modified zinc oxide;

[0054] Step (3) mixing epoxy resin, modified zinc oxide and toluene in a mass ratio of 200:80:2000, reacting at 60° C. for 5 h, filtering after the reaction, washing, and drying at 80° C. for 7 h to obtain modified zinc oxide grafted epoxy resin;

[0055] Step (4) adding the isocyanate-terminated polyurethane and the modified zinc oxide grafted epoxy resin to acetone, adding dibutyltin dilaurate, reacting at 80° C. for 38 hours, and after the reaction is completed, filtering, washing with anhydrous ethanol, and drying at 90° C. for 5 hours to obtain a modified polyurethane;

[0056] The modified polyurethane, BYK-024, deionized water, 1-phenoxy-2-propanol, ethylenediamine and KH550 were uniformly mixed in a mass ratio of 50:0.2:12:3:10:1 to obtain a coating;

[0057] The mass ratio of isocyanate-terminated polyurethane, modified zinc oxide grafted epoxy resin, acetone and dibutyltin dilaurate is 100:400:2500:1.5;

[0058] Step (5) polishing the duplex stainless steel surface with silicon carbide sandpaper, rinsing with deionized water, and drying with nitrogen, uniformly coating the coating on the treated duplex stainless steel surface, heating at 95° C. for 50 min to cure, and obtaining a corrosion-resistant duplex stainless steel pipe for marine engineering with a coating thickness of 30 μm.

[0059] Example 4

[0060] This embodiment provides a method for preparing a corrosion-resistant duplex stainless steel pipe for marine engineering, comprising the following steps:

[0061] Step (1) under an argon atmosphere, zinc oxide, 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine, N,N-dimethylformamide and potassium carbonate are mixed in a mass ratio of 65:280:2500:65, reacted at 50°C for 43h, the reaction was completed, filtered, washed with anhydrous ethanol, and dried at 85°C for 5.5h to obtain zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine;

[0062] Step (2) epoxy modified carbon fiber, zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine and 0.01 mol / L hydrochloric acid aqueous solution are mixed in a mass ratio of 25:575:7000, reacted at 70°C for 3.5 hours, filtered, washed with deionized water, and dried at 75°C for 7.5 hours to obtain modified zinc oxide;

[0063] Step (3) mixing epoxy resin, modified zinc oxide and toluene in a mass ratio of 250:85:2500, reacting at 65° C. for 4.5 hours, filtering after the reaction, washing, and drying at 85° C. for 6.5 hours to obtain modified zinc oxide grafted epoxy resin;

[0064] Step (4) adding the isocyanate-terminated polyurethane and the modified zinc oxide grafted epoxy resin to acetone, adding dibutyltin dilaurate, reacting at 85° C. for 35 h, and after the reaction is completed, filtering, washing with anhydrous ethanol, and drying at 95° C. for 4.5 h to obtain a modified polyurethane;

[0065] The modified polyurethane, BYK-024, deionized water, 1-phenoxy-2-propanol, ethylenediamine and KH550 were uniformly mixed in a mass ratio of 52:0.3:14:3.5:12:1.2 to obtain a coating;

[0066] The mass ratio of isocyanate-terminated polyurethane, modified zinc oxide grafted epoxy resin, acetone and dibutyltin dilaurate is 120:450:3000:1.8;

[0067] Step (5) polishing the duplex stainless steel surface with silicon carbide sandpaper, rinsing with deionized water, and drying with nitrogen, uniformly coating the coating on the treated duplex stainless steel surface, heating at 98° C. for 45 min to cure, and obtaining a corrosion-resistant duplex stainless steel pipe for marine engineering with a coating thickness of 30 μm.

[0068] Example 5

[0069] This embodiment provides a method for preparing a corrosion-resistant duplex stainless steel pipe for marine engineering, comprising the following steps:

[0070] Step (1) under an argon atmosphere, zinc oxide, 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine, N,N-dimethylformamide and potassium carbonate are mixed in a mass ratio of 70:310:3000:70, reacted at 55°C for 40h, the reaction is completed, filtered, washed with anhydrous ethanol, and dried at 90°C for 5h to obtain zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine;

[0071] Step (2) epoxy modified carbon fiber, zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine and 0.01 mol / L hydrochloric acid aqueous solution are mixed in a mass ratio of 30:650:8000, reacted at 75°C for 3h, filtered, washed with deionized water, and dried at 80°C for 7h to obtain modified zinc oxide;

[0072] Step (3) mixing epoxy resin, modified zinc oxide and toluene in a mass ratio of 300:90:3000, reacting at 70° C. for 4 h, filtering after the reaction, washing, and drying at 90° C. for 6 h to obtain modified zinc oxide grafted epoxy resin;

[0073] Step (4) adding the isocyanate-terminated polyurethane and the modified zinc oxide-grafted epoxy resin into acetone, adding dibutyltin dilaurate, reacting at 90° C. for 32 hours, filtering after the reaction, washing with anhydrous ethanol, and drying at 100° C. for 4 hours to obtain a modified polyurethane;

[0074] The modified polyurethane, BYK-024, deionized water, 1-phenoxy-2-propanol, ethylenediamine and KH550 were uniformly mixed in a mass ratio of 55:0.4:16:4:15:1.5 to obtain a coating;

[0075] The mass ratio of isocyanate-terminated polyurethane, modified zinc oxide grafted epoxy resin, acetone and dibutyltin dilaurate is 140:500:3500:2.1;

[0076] Step (5) polishing the duplex stainless steel surface with silicon carbide sandpaper, rinsing with deionized water, and drying with nitrogen, uniformly coating the coating on the treated duplex stainless steel surface, and curing by heating at 102° C. for 40 min to obtain a corrosion-resistant duplex stainless steel pipe for marine engineering with a coating thickness of 30 μm.

[0077] Example 6

[0078] This embodiment provides a method for preparing a corrosion-resistant duplex stainless steel pipe for marine engineering, comprising the following steps:

[0079] Step (1) under an argon atmosphere, zinc oxide, 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine, N,N-dimethylformamide and potassium carbonate are mixed in a mass ratio of 75:340:3500:75, reacted at 60°C for 37h, the reaction was completed, filtered, washed with anhydrous ethanol, and dried at 95°C for 4.5h to obtain zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine;

[0080] Step (2) epoxy modified carbon fiber, zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine and 0.01 mol / L hydrochloric acid aqueous solution are mixed in a mass ratio of 35:725:9000, reacted at 80°C for 2.5h, filtered, washed with deionized water, and dried at 85°C for 6.5h to obtain modified zinc oxide;

[0081] Step (3) epoxy resin, modified zinc oxide and toluene are mixed in a mass ratio of 350:95:3500, reacted at 75°C for 3.5 hours, filtered, washed and dried at 95°C for 5.5 hours to obtain modified zinc oxide grafted epoxy resin;

[0082] Step (4) adding the isocyanate-terminated polyurethane and the modified zinc oxide grafted epoxy resin to acetone, adding dibutyltin dilaurate, reacting at 95° C. for 29 hours, and after the reaction is completed, filtering, washing with anhydrous ethanol, and drying at 105° C. for 3.5 hours to obtain a modified polyurethane;

[0083] The modified polyurethane, BYK-024, deionized water, 1-phenoxy-2-propanol, ethylenediamine and KH550 were uniformly mixed in a mass ratio of 58:0.5:18:4.5:18:1.8 to obtain a coating;

[0084] The mass ratio of isocyanate-terminated polyurethane, modified zinc oxide grafted epoxy resin, acetone and dibutyltin dilaurate is 160:550:4000:2.4;

[0085] Step (5) polishing the duplex stainless steel surface with silicon carbide sandpaper, rinsing with deionized water, and drying with nitrogen, uniformly coating the coating on the treated duplex stainless steel surface, heating at 106° C. for 35 min to cure, and obtaining a corrosion-resistant duplex stainless steel pipe for marine engineering with a coating thickness of 30 μm.

[0086] Example 7

[0087] This embodiment provides a method for preparing a corrosion-resistant duplex stainless steel pipe for marine engineering, comprising the following steps:

[0088] Step (1) under an argon atmosphere, zinc oxide, 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine, N,N-dimethylformamide and potassium carbonate are mixed in a mass ratio of 80:370:4000:80, reacted at 65°C for 34 hours, filtered, washed with anhydrous ethanol, and dried at 100°C for 4 hours to obtain zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine;

[0089] Step (2) epoxy modified carbon fiber, zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine and 0.01 mol / L hydrochloric acid aqueous solution are mixed in a mass ratio of 40:800:10000, reacted at 85°C for 2h, filtered, washed with deionized water, and dried at 90°C for 6h to obtain modified zinc oxide;

[0090] Step (3) mixing epoxy resin, modified zinc oxide and toluene in a mass ratio of 400:100:4000, reacting at 80° C. for 3 h, filtering after the reaction is completed, washing, and drying at 100° C. for 5 h to obtain modified zinc oxide grafted epoxy resin;

[0091] Step (4) adding the isocyanate-terminated polyurethane and the modified zinc oxide-grafted epoxy resin into acetone, adding dibutyltin dilaurate, reacting at 100° C. for 26 hours, filtering after the reaction, washing with anhydrous ethanol, and drying at 110° C. for 3 hours to obtain a modified polyurethane;

[0092] The modified polyurethane, BYK-024, deionized water, 1-phenoxy-2-propanol, ethylenediamine and KH550 were uniformly mixed in a mass ratio of 60:0.6:20:5:20:2 to obtain a coating;

[0093] The mass ratio of isocyanate-terminated polyurethane, modified zinc oxide grafted epoxy resin, acetone and dibutyltin dilaurate is 180:600:4500:2.7;

[0094] Step (5) polishing the duplex stainless steel surface with silicon carbide sandpaper, rinsing with deionized water, and drying with nitrogen, uniformly coating the coating on the treated duplex stainless steel surface, heating at 110° C. for 30 min to cure, and obtaining a corrosion-resistant duplex stainless steel pipe for marine engineering with a coating thickness of 30 μm.

[0095] Comparative Example 1

[0096] This comparative example provides a method for preparing a corrosion-resistant duplex stainless steel pipe for marine engineering, comprising the following steps:

[0097] Step (1) under an argon atmosphere, zinc oxide, 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine, N,N-dimethylformamide and potassium carbonate are mixed in a mass ratio of 60:250:2000:60, reacted at 45°C for 46 hours, filtered, washed with anhydrous ethanol, and dried at 80°C for 6 hours to obtain zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine;

[0098] Step (2) epoxy modified carbon fiber, zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine and 0.01 mol / L hydrochloric acid aqueous solution are mixed in a mass ratio of 20:500:6000, reacted at 65°C for 4h, filtered, washed with deionized water, and dried at 70°C for 8h to obtain modified zinc oxide;

[0099] Step (3) mixing epoxy resin, modified zinc oxide and toluene in a mass ratio of 200:80:2000, reacting at 60° C. for 5 h, filtering after the reaction, washing, and drying at 80° C. for 7 h to obtain modified zinc oxide grafted epoxy resin;

[0100] Step (4) uniformly mixing the modified zinc oxide grafted epoxy resin, BYK-024, deionized water, 1-phenoxy-2-propanol, ethylenediamine and KH550 in a mass ratio of 50:0.2:12:3:10:1 to obtain a coating;

[0101] Step (5) polishing the duplex stainless steel surface with silicon carbide sandpaper, rinsing with deionized water, and drying with nitrogen, uniformly coating the coating on the treated duplex stainless steel surface, heating at 95° C. for 50 min to cure, and obtaining a corrosion-resistant duplex stainless steel pipe for marine engineering with a coating thickness of 30 μm.

[0102] Comparative Example 2

[0103] This comparative example provides a method for preparing a corrosion-resistant duplex stainless steel pipe for marine engineering, comprising the following steps:

[0104] Step (1) under an argon atmosphere, zinc oxide, 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine, N,N-dimethylformamide and potassium carbonate are mixed in a mass ratio of 60:250:2000:60, reacted at 45°C for 46 hours, filtered, washed with anhydrous ethanol, and dried at 80°C for 6 hours to obtain zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine;

[0105] Step (2) epoxy modified carbon fiber, zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine and 0.01 mol / L hydrochloric acid aqueous solution are mixed in a mass ratio of 20:500:6000, reacted at 65°C for 4h, filtered, washed with deionized water, and dried at 70°C for 8h to obtain modified zinc oxide;

[0106] Step (3) physically mixing the epoxy resin and the modified zinc oxide in a mass ratio of 200:80, stirring at a speed of 200 r / min for 18 min to obtain a modified epoxy resin;

[0107] Step (4) The modified epoxy resin, BYK-024, deionized water, 1-phenoxy-2-propanol, ethylenediamine and KH550 are mixed uniformly in a mass ratio of 50:0.2:12:3:10:1 to obtain a coating;

[0108] Step (5) polishing the duplex stainless steel surface with silicon carbide sandpaper, rinsing with deionized water, and drying with nitrogen, uniformly coating the coating on the treated duplex stainless steel surface, heating at 95° C. for 50 min to cure, and obtaining a corrosion-resistant duplex stainless steel pipe for marine engineering with a coating thickness of 30 μm.

[0109] The epoxy-modified carbon fibers in Examples 3-7 and Comparative Examples 1-2 all adopt the epoxy-modified carbon fibers prepared in Example 1; the isocyanate-terminated polyurethanes in Examples 3-7 all adopt the isocyanate-terminated polyurethanes prepared in Example 2.

[0110] The carbon fibers in the examples and comparative examples were from Shanghai Aladdin Biochemical Technology Co., Ltd.; dimethyl biphenyl diisocyanate was from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., CAS No.: 91-97-4, content: 99%; 1,4-butanediol was from Guangdong Yuemei Chemical Co., Ltd., CAS No.: 110-63-4; dimethyl sulfoxide was from Shandong Cosmay New Materials Co., Ltd., CAS No.: 67-68-5, purity: 99.9%; zinc oxide was nanostructured and was from Nanjing Baoket New Materials Co., Ltd., model PZT-30, with an average particle size of 30 nm; 2-(4 -Chloro-phenyl)-2H-benzotriazole-5-ylamine was from Shanghai Heling Xinde Pharmaceutical Research Co., Ltd., CAS No.: 40655-09-2; the epoxy resin was bisphenol A epoxy resin, from Shenzhen Yoshida Chemical Co., Ltd., with a solid content of 100%, and was a colorless, transparent liquid; BYK-024 was from BYK Company of Germany; tetrahydrofuran was purchased from Shaanxi Ruijia Youhao Chemical Co., Ltd., CAS No.: 109-99-9; 1-phenoxy-2-propanol was from Shanghai MacLean Biochemical Technology Co., Ltd., CAS No.: 770-35-4; other products were all commercially available products.

[0111] Corresponding tests were performed on the corrosion-resistant duplex stainless steel pipes for marine engineering prepared in Examples 3-7 and Comparative Examples 1-2. The test results are as follows:

[0112] (1) Adhesion test: The coating adhesion on the surface of the corrosion-resistant duplex stainless steel pipe for marine engineering was tested according to the standard GB / T 5210-2006 "Determination of coating adhesion - Pull-off method". The specific test results are shown in Table 1.

[0113] (2) Corrosion resistance test: The corrosion-resistant duplex stainless steel pipes for marine engineering to be tested were immersed in 5% sodium oxide solution, and the samples were suspended with plastic ropes, with the upper end greater than 2 cm from the liquid surface. The pH value of the solution was 6.5. The salt water was replaced every six days and the samples were left open at a temperature of 10 ± 2 °C. The time when the first rust spot appeared on each sample was recorded as the corrosion resistance time, and the 72h plane corrosion degree was recorded at the same time. The specific results are shown in Table 1.

[0114] Table 1

[0115]

[0116] It can be seen from Table 1 that the corrosion-resistant duplex stainless steel pipe for marine engineering prepared by the present invention has good corrosion resistance, especially Example 3 has the best effect, and the coating on the surface of the corrosion-resistant duplex stainless steel pipe for marine engineering in Example 3 has good adhesion, prevents falling off, and is conducive to extending the service life. Compared with Example 1, Comparative Example 1 lacks the isocyanate-terminated polyurethane. The epoxy groups in the epoxy resin in Comparative Example 1 form more hydrogen bonds with the metal surface and have better adhesion. However, the lack of isocyanate-terminated polyurethane cannot reduce the voids in the epoxy resin itself, and the density is reduced, resulting in the inability to prolong the time for chloride ions and water to enter the coating and contact the metal surface to cause corrosion and damage, and the corrosion resistance time is reduced compared with Example 1. The amino groups in the modified zinc oxide in Comparative Example 1 undergo a ring-opening reaction and connect with the epoxy groups in the epoxy resin, which increases the compatibility and is conducive to uniform corrosion protection. Compared with Comparative Example 1, Comparative Example 2 adopts physical mixing to neutralize the modified zinc oxide and the epoxy resin, and its compatibility and dispersibility are lower than those of Comparative Example 1. Therefore, the adhesion of Comparative Example 2 is lower than that of Comparative Example 1, the corrosion resistance time is lower than that of Comparative Example 1, and the 72h plane corrosion degree is greater than that of Comparative Example 1.

[0117] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing a corrosion-resistant duplex stainless steel pipe for marine engineering, characterized in that: The following steps are involved: Step (1) in an inert gas, zinc oxide and 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine are added to N,N-dimethylformamide, potassium carbonate is added, heating is performed, reacting is performed, the reaction is completed, filtering is performed, washing is performed, and drying is performed to obtain zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine; Step (2) adding epoxy-modified carbon fiber and zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine to a hydrochloric acid aqueous solution, heating, reacting, filtering, washing, and drying after the reaction is completed to obtain modified zinc oxide; Step (3) adding epoxy resin and modified zinc oxide into toluene, heating, reacting, filtering, washing and drying after the reaction is completed to obtain modified zinc oxide grafted epoxy resin; Step (4) adding the isocyanate-terminated polyurethane and the modified zinc oxide-grafted epoxy resin into acetone, adding a catalyst, reacting, filtering after the reaction is completed, washing, and drying to obtain a modified polyurethane; The modified polyurethane, defoamer, deionized water, film former, curing agent and adhesion promoter are uniformly mixed to obtain a coating; Step (5) polishes, rinses and blows the surface of the duplex stainless steel, uniformly applies the coating on the treated surface of the duplex stainless steel, heats and solidifies it, and obtains a corrosion-resistant duplex stainless steel pipe for marine engineering.

2. The method for preparing a corrosion-resistant duplex stainless steel pipe for marine engineering according to claim 1, characterized in that: The mass ratio of zinc oxide, 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine, N,N-dimethylformamide and potassium carbonate is (60-80):(250-370):(2000-4000):(60-80); the reaction temperature is 45-65°C, and the reaction time is 34-46h.

3. The method for preparing a corrosion-resistant duplex stainless steel pipe for marine engineering according to claim 1, characterized in that: The mass ratio of epoxy modified carbon fiber, zinc oxide grafted 2-(4-chloro-phenyl)-2H-benzotriazole-5-ylamine and hydrochloric acid aqueous solution is (20-40):(500-800):(6000-10000); the reaction temperature is 65-85°C, the reaction time is 2-4h; the concentration of hydrochloric acid aqueous solution is 0.01mol / L.

4. The method for preparing a corrosion-resistant duplex stainless steel pipe for marine engineering according to claim 1, characterized in that: The mass ratio of epoxy resin, modified zinc oxide and toluene is (200-400):(80-100):(2000-4000); the reaction temperature is 60-80°C, and the reaction time is 3-5h.

5. The method for preparing a corrosion-resistant duplex stainless steel pipe for marine engineering according to claim 1, characterized in that: The mass ratio of isocyanate-terminated polyurethane, modified zinc oxide grafted epoxy resin, acetone and catalyst is (100-180):(400-600):(2500-4500):(1.5-2.7); the reaction temperature is 80-100° C., and the reaction time is 26-38 hours.

6. The method for preparing a corrosion-resistant duplex stainless steel pipe for marine engineering according to claim 1, characterized in that: The catalyst is dibutyltin dilaurate.

7. The method for preparing a corrosion-resistant duplex stainless steel pipe for marine engineering according to claim 1, characterized in that: The preparation method of isocyanate-terminated polyurethane comprises the following steps: Add dimethylbiphenyl diisocyanate and 1,4-butanediol to a solvent, stir evenly, heat, react, add a protective agent, react, and after the reaction is completed, perform reduced pressure distillation to obtain an intermediate I; The intermediate I is added to tetrahydrofuran, methanol is added, filtered, washed and dried to obtain an isocyanate-terminated polyurethane.

8. The method for preparing a corrosion-resistant duplex stainless steel pipe for marine engineering according to claim 1, characterized in that: The preparation method of epoxy modified carbon fiber comprises the following steps: The carbon fiber, anhydrous ethanol and γ-(2,3-epoxypropoxy)propyltrimethoxysilane are uniformly mixed, heated, reacted, centrifuged, washed and dried after the reaction is completed to obtain epoxy-modified carbon fiber.

9. The method for preparing a corrosion-resistant duplex stainless steel pipe for marine engineering according to claim 1, characterized in that: The mass ratio of modified polyurethane, defoamer, deionized water, film former, curing agent and adhesion promoter is (50-60):(0.2-0.6):(12-20):(3-5):(10-20):(1-2).

10. A corrosion-resistant duplex stainless steel pipe for marine engineering prepared by the method for preparing a corrosion-resistant duplex stainless steel pipe for marine engineering according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A high-temperature resistant heavy-duty anti-corrosion coating for stainless steel

    CN108178984B

  • High-adhesion powder coating for stainless steel and its preparation method

    CN111718642B

  • Preparation method of galvanized steel sheet with wear-resistant coating

    CN116285593A

  • Corrosion-resistant anti-ultraviolet film and preparation method and application thereof

    CN116622172A